Ukraine : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Ukraine during 1991-95. In October 1994, Ukraine finally embarked upon a comprehensive program of economic reform and stabilization. Although the efforts made in late 1994 were far reaching, the short-term results were not encouraging: inflation remained stubbornly high, the exchange rate weak, activity declined, and the rate of accumulation of external arrears dangerously rapid. By the first half of 1995, the performance .of the economy was more encouraging. Inflation slowed to monthly rates of about 5 percent. Exports to western markets also expanded strongly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet